Clinical features and treatment with botulinum toxin in blepharospasm: a 17-year experience - Aquino, Camila Catherine [UNIFESP] (2012)
OBJECTIVE: It was to analyze clinical aspects of patients with blepharospasm, including outcomes of botulinum toxin treatment. Additionally, clinical characteristics of isolated blepharospasm were compared to those of blepharospasm plus other movement disorders. METHODS: Clinical data recorded during 17 years were reviewed. The variables included age, gender, age of onset, past medical history, head trauma, smoking history, family history of dystonia, severity, duration of botulinum toxin relief and adverse effects. RESULTS: A total of 125 patients were included and 75.2% were female. The mean age of onset was 54.3 years; 89.6% of the individuals started with contractions in eye region, and 39.2% of them spread to lower face or neck. Isolated blepharospasm group was compared with blepharospasm-plus group for demographic and clinical features, and therapeutic outcomes, without significant differences. Botulinum toxin treatment improved the severity of contractions (p=0.01) with low rate of side effects (14%). CONCLUSIONS: Both groups - isolated blepharospasm and blepharospasm-plus - shared similar results concerning epidemiology, clinical features and therapeutic response to botulinum toxin.